2001
DOI: 10.1021/jp010628b
|View full text |Cite
|
Sign up to set email alerts
|

Supported Tantalum Oxide and Supported Vanadia-tantala Mixed Oxides: Structural Characterization and Surface Properties

Abstract: Silica-, alumina-, and zirconia-supported tantalum oxide and supported vanadia-tantala mixed oxide catalysts were investigated by XRD, UV-vis-DR, FTIR, and FT-Raman spectroscopy to determine the nature of the surface tantala species. Two types of surface TaO x species were identified. On the SiO 2 support, at low coverages tetrahedral TaO 4 species exist, with a TadO bond and three bridging Ta-O-support bonds. At higher coverages, octahedral TaO 6 species occur. On Al 2 O 3 and ZrO 2 both surface species exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 54 publications
3
50
0
9
Order By: Relevance
“…Therefore, monolayer coverage or maximum dispersion limit is a critical parameter that allows distinguishing between two-dimensional molecularly dispersed surface metal oxide species and the three-dimensional NPs present in supported metal oxide materials. For the purposes of simplifying and focusing the discussion, only SiO 2 -supported metal oxide catalysts at submonolayer coverages will be discussed in this chapter since the catalysis literature has demonstrated that only isolated surface metal oxide species are present at low coverage for supported MO x /SiO 2 catalysts [14,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, monolayer coverage or maximum dispersion limit is a critical parameter that allows distinguishing between two-dimensional molecularly dispersed surface metal oxide species and the three-dimensional NPs present in supported metal oxide materials. For the purposes of simplifying and focusing the discussion, only SiO 2 -supported metal oxide catalysts at submonolayer coverages will be discussed in this chapter since the catalysis literature has demonstrated that only isolated surface metal oxide species are present at low coverage for supported MO x /SiO 2 catalysts [14,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Alguns óxidos de metais do grupo V, como tântalo e vanádio, e óxido de alumínio USHIKUBO;WADA, 1995;BALTES et al, 2001;ARGYLE et al, 2004;MARTINEZ-HUERTA et al, 2006;CORTEZ et al, 2003) vêm sendo estudados em busca de uma melhor performance. (LIETTI et al, 1999).…”
Section: Lista De Figurasunclassified
“…O catalisador ternário vanadiatântala-suporte é potencialmente útil em reações que necessitem tanto de sítios ácidos como redox (BALTES et al, 2001). …”
Section: Lista De Figurasunclassified
See 2 more Smart Citations